Pengembangan Multimedia Interaktif Melalui Smart Apps Creator (SAC) Pada Mata Pelajaran IPAS di Kelas IV SD - Mayanty, Sri; Rosa, Novrita Mulya; Astriani, Maya Masitha (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
Science learning in elementary school which is the basis of physics, chemistry and biology, emphasizes that learning does not only involve knowledge issues but emphasizes more on how students learn and the effects of the learning process. In science learning, a process is needed that can stimulate students to learn, but in reality in the field students often find it difficult to understand science concepts and assume that science learning is difficult. Based on the problems and circumstances of these students, an interactive multimedia development based on Android is needed. The development model in this study uses ADDIE, which includes Analysis, Design, Development, Implementation and Evaluation. Based on the validation results from various experts, the data obtained were the results of media expert validation obtained an average score of 92.5% with the interpretation of "very feasible", the results of material expert validation obtained an average score of 84.28% with the interpretation of "very feasible" and the results of language expert validation obtained an average score of 92.7% with the interpretation of "very feasible". And the results of the trial conducted on grade IV students of SDN Jagakarsa 14 obtained an average score of 9.43% with the interpretation of "very feasible". The results show that Android-based interactive multimedia on work and business materials is very suitable for use as a medium in the learning process.